2019
DOI: 10.1007/s10851-019-00916-w
|View full text |Cite
|
Sign up to set email alerts
|

A Proximal Interior Point Algorithm with Applications to Image Processing

Abstract: In this article, we introduce a new proximal interior point algorithm (PIPA). This algorithm is able to handle convex optimization problems involving various constraints where the objective function is the sum of a Lipschitz differentiable term and a possibly nonsmooth one. Each iteration of PIPA involves the minimization of a merit function evaluated for decaying values of a logarithmic barrier parameter. This inner minimization is performed thanks to a finite number of subiterations of a variable metric forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…However, solving exactly each subproblem P γj with a given algorithm is practically impossible and not desirable for computational time reasons. When R is differentiable, the following proposed inexact exterior penalty method, inspired by [22], [23], allows an inexact resolution (i.e., early stopping) for the sequence of subproblems (P γj ) j∈N , while still benefiting from the same convergence properties as above.…”
Section: Proposed Exterior Penalty Framework a Exact Exterior Penalty Methodsmentioning
confidence: 99%
“…However, solving exactly each subproblem P γj with a given algorithm is practically impossible and not desirable for computational time reasons. When R is differentiable, the following proposed inexact exterior penalty method, inspired by [22], [23], allows an inexact resolution (i.e., early stopping) for the sequence of subproblems (P γj ) j∈N , while still benefiting from the same convergence properties as above.…”
Section: Proposed Exterior Penalty Framework a Exact Exterior Penalty Methodsmentioning
confidence: 99%
“…The integrated heuristics of PSO-IPM is exploited to train the networks, while the essential parameter settings of importance elements for PSO-IPM are given in Table 1. Few recently IP scheme applications are power flow security constraint optimization (Casacio et al 2019), image processing (Chouzenoux et al 2020), multistage nonlinear nonconvex problems (Zanelli et al 2020) and nonlinear benchmark models (Wambacq et al 2021). The PSO-IP scheme is used to train the networks as per process and parameter settings provided in Table 1.…”
Section: Optimization: Pso-ipmmentioning
confidence: 99%
“…Standard interior point methods require to invert several n × n linear systems, which leads to a high computational complexity for large scale problems. Nonetheless, it has recently been shown that combining the interior point framework with a proximal forward-backward strategy [44,45] leads to very competitive solvers for inverse problems [46,47,48].…”
Section: Interior Point Approachesmentioning
confidence: 99%